Chloroquine- and Hydroxychloroquine–Induced Cardiomyopathy: A Case Report and Brief Literature Review. Issue 6 (14th December 2020) - Nadeem, Urooba; Raafey, Muhammad; Kim, Gene; Treger, Jerermy; Pytel, Peter; N Husain, Aliya; Schulte, Jefree J
Abstract: Objectives: To present an index case and review the histologic and electron microscopic findings in chloroquine (CQ) and hydroxychloroquine (HCQ) myopathy, focusing primarily on cardiomyopathy. CQ and HCQ are antimalarial drugs with disease-modifying activity in rheumatic diseases (DMARD) and now are among the most widely used DMARDs. Although they are rare, severe adverse effects caused mainly by deposition of intracellular metabolites in both cardiac and skeletal muscle have been described. Currently, both CQ and HCQ have been proposed to have efficacy for patients with coronavirus disease 2019, and several large centers in the United States and other countries have started clinical trials. Methods: A case of HCQ cardiotoxicity diagnosed on an endomyocardial biopsy is presented. A review of the pathology archives was performed to identify additional cases of CQ or HCQ myopathy, and histologic changes were recorded. A brief literature review with an emphasis on pathologic findings in myopathies was performed. Results: Including the index case, 4 cases of CQ or HCQ myopathy were identified. Light microscopic findings included vacuolated myopathy, and electron microscopic findings included myeloid bodies and curvilinear inclusion bodies. Conclusion: CQ and HCQ myopathy can present following long-term administration of the drug. The pathologic findings are nonspecific and overlap with other vacuolated myopathies, necessitating careful correlation of the histologic changes with the patient's medical history.